MODERN PARADIGM OF THE FORENSIC SIGNIFICANCE OF DIGITAL TRACES IN CRIMINAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2025)
The article examines the nature of digital traces as elements of the information environment created by criminal activity in the digital space. It establishes that digital traces can serve as forensically significant sources of information capable of revealing the mechanism of the crime, the identity of the offender, the circumstances of the incident, and other relevant details vital for evidence. The distinction between digital traces and traditional material carriers of trace information is clarified, particularly their instability, intangibility, susceptibility to external interference, and the difficulty of fixation. It is highlighted that these features necessitate adapting current forensic methods and developing new techniques for the fixation, verification, preservation, and evaluation of digital information as evidence. Several critical issues related to regulatory frameworks for handling digital traces in criminal proceedings are outlined, including the absence of a clear definition of electronic evidence, vague admissibility criteria, and inadequate procedural documentation of actions involving digital media. The need to unify terminology and procedures in line with international standards, especially those outlined in the Budapest Convention and the recommendations of the Council of Europe, is also emphasized.
Keywords: forensics; trace; digital trace; electronic evidence; proving; evidence collection; digital space